Parametrization of the mechanically induced self-propagating high-temperature synthesis (MI-SHS) of Ti5Si3 - Juárez Arellano, Erick Adrián; Martínez García, Alfredo; Winkler, B.; Pérez López, Tezozomoc; Padilla, J. M. (Elsevier, 2023)
Mechanically activated self-propagating high-temperature synthesis (MA-SHS) is one of the most used methodologies to synthesize titanium silicides, especially Ti5Si3. However, the problem in this methodology is to know the milling conditions needed to mechanically activate (MA) or mechanically induce (MI) the reaction of the starting materials. This information is fundamental for obtaining reproducible results. Therefore, the parametrization of the mechanically induced self-propagating high-temperature synthesis (MI-SHS) of Ti5Si3 is explored in the present study. A simple kinematic approach is used to parametrise the mechanically induced reaction as a function of the milling parameters, such as the angular velocity of the mill and the grinding time. The accumulated and transferred energy per hit needed to induce the MI-SHS of Ti5Si3 are predicted. A kinetic approach that allows the complete parametrization of mechanically induced reactions is also used.
Keywords: Compuestos intermetálicos; Molino de bolas de alta energía; Mecanoquímica; Parametrización